2004
DOI: 10.1029/2003jf000115
|View full text |Cite
|
Sign up to set email alerts
|

Footwall topographic development during continental extension

Abstract: [1] We examine the progressive development of footwall topography associated with a set of active normal faults in the northeastern Basin and Range Province of the western United States. Fault length and displacement increase monotonically from northeast to southwest in the study area, allowing us to track both variations in footwall morphology with increasing displacement and along-strike changes in morphology on a single fault. We show that patterns of catchment area, footwall relief, and catchment outlet sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 47 publications
6
119
0
1
Order By: Relevance
“…Fault initiation and uplift occurred at~6 Ma for the Lost River, Lemhi, and Beaverhead faults, and each range-front fault is divided along-strike into six fault segments (Densmore et al, 2005). In a series of studies Densmore et al (2004Densmore et al ( , 2005Densmore et al ( , 2007 investigated relationships between fault development and footwall topography in each range, and concluded that, away from the developing southern fault tips, footwall relief remains relatively constant and is limited by colluvial processes on steep threshold hillslopes.…”
Section: Study Areamentioning
confidence: 98%
“…Fault initiation and uplift occurred at~6 Ma for the Lost River, Lemhi, and Beaverhead faults, and each range-front fault is divided along-strike into six fault segments (Densmore et al, 2005). In a series of studies Densmore et al (2004Densmore et al ( , 2005Densmore et al ( , 2007 investigated relationships between fault development and footwall topography in each range, and concluded that, away from the developing southern fault tips, footwall relief remains relatively constant and is limited by colluvial processes on steep threshold hillslopes.…”
Section: Study Areamentioning
confidence: 98%
“…Normal faults (and in Kåfjord, many gravitationally failing rock hillsides; see Henderson et al, 2011) exhibit a distinctive and diagnostic morphology (e.g., Dawers et al, 1993;Destro, 1995;Burbank & Anderson, 2001;Densmore et al, 2004). They have no scarp at the tip (the point past which surface rupture has not propagated) and rise to a maximum scarp height near the midpoint of the ruptured segment.…”
Section: Theoretical Issuesmentioning
confidence: 99%
“…2) to the Scandinavian onshore topographic envelope along 234 profiles oriented parallel to the direction of tectonic transport and confirmed the correlation between crustal thinning and rifted margin escarpment elevation for Scandinavia. They also documented the geometric relationships between crustal taper and hinterland river drainages, proximal domain brittle fault fabrics, and juxtaposed landscapes that are predicted by the simple principles of tectonic geomorphology (e.g., Leeder & Gawthorpe, 1987;Leeder & Jackson, 1993;Gawthorpe & Leeder, 2000;Burbank & Anderson, 2001;Densmore et al, 2004). Redfield & Osmundsen (2013) suggested that footwall uplift, driven by erosion and deposition and governed by the thinning gradient, was responsible for much of Scandinavia's Cenozoic topographic rejuvenation.…”
Section: The Taper Hypothesismentioning
confidence: 99%